Postrzeganie starości przez kobiety i mężczyzn w wieku 75 plus = Perception of senility by women and men aged 75 plus - Herudzińska, Małgorzata H. (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the results of research on perception of senility carried out among 170 individuals (women and men) aged 75 plus. The research was carried out using the technique of compartmentalized interview. The results show that elders are prone to point to big shortcomings of the age they have reached. Individuals rarely expose positive aspects of senility, and their opinions fit the promotion of "active ageing" ideas to a very limited extent.
Keywords: starość; stereotypy starości; płeć; stereotypy płci; senility; stereotypes of senility; gender; stereotypes of sexes